THE TEACHERS’ ROLES IN AN ONLINE ENGLISH TEACHING - Ni Made Gita Anggriani; Luh Putu Artini; Ni Putu Era Marsakawati (Lingua Scientia, 2022)
AbstractThis study aims to explain a) the role of the English teacher at one of the private junior high schools during online teaching activities, b) the difficulties faced by them when using e-platforms for online learning, and c) strategies used by them when teaching online through e-learning platforms. The research design used was qualitative descriptive. The research subjects were two English teachers. Data were collected through questionnaires, observation, and interviews. Data were analyzed qualitatively. The results of the data analysis show that a) there were eight roles played by the teacher in the online learning when teaching English; b) the difficulties found by the English teachers were the limited internet access and devices that prevent students from participating in online classes, and c) the strategies used by the teachers were using various online learning platforms and varying their teaching techniques.